STRATEGI KOMUNIKASI PEMASARAN TERPADU MEDIA CETAK LOKAL DALAM MENGHADAPI ERA KOMPETITIF: Studi Pada Radar Depok dan Radar Bogor - Yayu Sriwartini (Jurnal Ilmu dan Budaya, 2016)
The media industry in Indonesia had been expanding, including the local newspapers. Radar Depok and Radar Bogor were two local newspapers that had to compete with the national newspapers. Based on that background, this research was intended to describe the marketingcommunication strategy of Radar Radar Depok and Radar Bogor in attracting customers in the competitive era. This research approach was qualitative with the case study method. The main technique of data was indepth interview with the head of the marketing division of each newspaper. Another tehnique was review of some literatures . To prevent that the datas had validity, the researcher used some triangulations tehniques. The result showed that Radar Bogor implemented both of push and pull marketing communictaion. IT was better than Radar Depok.